1998
DOI: 10.3402/tellusb.v50i4.16131
|View full text |Cite
|
Sign up to set email alerts
|

Concentration, size-distribution and deposition of mineral aerosol over Chinese desert regions

Abstract: The mass-particle size distributions (MSDs) of 9 elements in ground-based aerosol samples from dust storm (DS) and non-dust storm (N-DS) periods were determined for 12 sites in 9 major desert regions in northern China. The masses of the 9 elements (Al, Fe, K, Mg, Mn, Sc, Si, Sr and Ti) in the atmosphere were dominated by local mineral dust that averaged 270 mg m−3, and the MSDs for the elements were approximately log-normal. On the basis of Al data, the <10 mm particles account for~84% of the total dust mass o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 17 publications
7
60
0
Order By: Relevance
“…Nevertheless, an extreme value of 664 mg m -2 h -1 was recorded on March 2011, during a strong dust storm in Kuwait that was a local phenomenon. This extreme dust loading were comparable to sites primarily that are affected by a local dust sources [20]. The temporal variations of the deposition rates showed seasonal tendency, as presented in Fig.…”
Section: Resultssupporting
confidence: 74%
“…Nevertheless, an extreme value of 664 mg m -2 h -1 was recorded on March 2011, during a strong dust storm in Kuwait that was a local phenomenon. This extreme dust loading were comparable to sites primarily that are affected by a local dust sources [20]. The temporal variations of the deposition rates showed seasonal tendency, as presented in Fig.…”
Section: Resultssupporting
confidence: 74%
“…Studies of dust loadings and fluxes have suggested that there are two main source areas: the Taklimakan and the Badain Juran (Zhang et al, 1998). The Tarim basin experiences some of the most frequent and intense dust storm occurrences on Earth (Zhang, Arimoto and An, 1997).…”
Section: Chinamentioning
confidence: 99%
“…Table I shows the concentrations and ratios of crustal components in PM 10 during the dust storm events. The first dataset in this table is extracted from Zhang et al (1998), showing the average atmospheric concentrations of elements in 9 samples from Chinese desert regions (such as Gobi, Taklimakan, Mu Us, Badain Juran Desert, etc.) during dust storm periods.…”
Section: Chemical Properties Of Dust Storm Samplesmentioning
confidence: 99%
“…Chinese desert regions are widely considered to be the major sources for Asian dust (Zhang et al, 1998). Dust storms (DS) occur frequently in spring (Zhou et al, 1996) over desert or loess areas due to the low rainfall and high frequency of strong winds associated with cold fronts.…”
Section: Introductionmentioning
confidence: 99%